To pill or not to pill in GnRH-antagonist cycles: the answer is in the data already!. Issue 1 (July 2015) - Griesinger, Georg; Venetis, Christos A.; Tarlatzis, Basil; Kolibianakis, Efstratios Michaelis
Abstract The planning of IVF treatment by scheduling menstruation and hence initiation of ovarian stimulation using sex-steroid pre-treatment is commonly used. Pooling data from six randomized-controlled trials encompassing 1343 patients, with and without combined oral contraceptive pill pre-treatment, suggests that the ongoing pregnancy rate per randomized woman is significantly lower in patients with oral contraceptive pill pre-treatment (relative risk [RR]: 0.80, 95% confidence interval [CI]: 0.66–0.97; rate difference [RD]: −5%, 95% CI: −10% to −1%; fixed effects model). This finding remains remarkably robust in multiple sensitivity analyses: exclusion of a study on poor responders, exclusion of the three smallest studies or exclusion of studies with a pill-free interval of less than 5 days, results in RR of 0.78 (95% CI: 0.64–0.94), 0.80 (95% CI: 0.65–0.98) and 0.79, (95% CI: 0.64–0.99), respectively. Furthermore, the finding of a significant reduction in ongoing pregnancy rate is not inconsistent with other evidence from the literature. The potential benefit of using oral contraceptive pill pre-treatment for cycle planning should therefore be balanced against its detrimental effect. Further randomized studies should test whether an effect similar to the one observed after combined oral contraceptive pill usage exists after other sex steroid pre-treatment regimens.